Dermal fillers facial anatomy and injection techniques - Braz, André (André Vieira) (Thieme, 2021)
"In-depth and detailed knowledge of anatomy, different facial shapes, and ethnic origins is essential to delivering safe, effective, natural, and harmonious aesthetic facial treatment results. Dermal Fillers: Facial Anatomy and Injections Techniques is the culmination of many years of expertise decrypting facial anatomy as it applies to aesthetic enhancement of the face. This visually rich atlas is authored by internationally renowned Brazilian dermatologists André Vieira Braz, an esteemed expert in the use of botulinum toxin, fillers, and lasers; and Thais Sakuma, a distinguished lecturer in the application of botulinum toxin and hyaluronic acid fillers. Nineteen highly practical, concise, and didactic chapters are organized consistently with structured text at the beginning of each chapter. The book encompasses the application of injection techniques for the full spectrum of indications, from softening wrinkles to facial contouring. Important topics include facial assessment, hyaluronic acid science, facial aging, and regional nerve blocks for pain management. Meticulous anatomic descriptions and images depict the relationships between superficial and deeper structures such as vasculature, thereby providing vital knowledge to help clinicians avoid potentially serious complications"--